Innovative methods of teaching in higher education and improving traditional methods with them - Murodullaev, Bakhtiyor; Khaknazarova, Dilobar (MMIT Proceedings, 2024)
The traditional teaching methodology is outdated, and it is necessary to determine the best ways to improve the skills of teachers and students. In order to develop durable and able-bodied skills, there is a need to change pedagogy from a traditional lecture based on facts to an interactive teaching. To solve this problem, innovation is important in teaching and training. As mentioned in the article, the adoption of various methods and strategies will help to achieve the desired result. This article describes innovative methods of teaching, which are being introduced in higher educational institutions of our country.